Evaluation on usage of Islamic financing contracts in Malaysia: A comparative study of Bank Islam and Bank Muamalat - Abdul Razak, Dzuljastri; Abdul Hameed, Abdul Wahab (2015)

(untitled)
Literature review on Islamic banking and finance revealed that trade-based products such as Murabahah and BBA are widely used financial instruments in Islamic banks. Nonetheless, these two instruments are also known to be controversial. They are seen as instruments that promote consumerism by financing consumer goods rather than entrepreneurial activities such as Musharakah and Mudharabah. Due to the criticisms, some banks are said to be gradually moving from the use of BBA to other forms of Islamic financing. This study investigates the extent to which the concepts of Murabahah and BBA are being used. Secondly, it examines whether there are other concepts that being used to replace them. The findings indicated that the concept of BBA was indeed widely used while the use of murabahah is very minimal. However, banks are gradually shifting to new concepts such as Commodity Murabahah and Tawarruq. Nonetheless, both these concepts as practiced in Malaysia are still based on debt which is less superior than Mudharabah and Musharakah in meeting the true objectives of Maqasid Al Shariah.